2017
DOI: 10.21608/bvmj.2017.30515
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence genes of enterotoxigenic Staphylococcus aureus isolated from chicken meat cuts by using PCR

Abstract: The present study was performed on 120 random samples of fresh chicken meat cuts of Drumstick, thigh and breast (40 of each) which were purchased from different supermarkets and retail chicken butchers at Kaliobia Governorate, for detection of virulence genes responsible for Staphylococcus. aureus enterotoxins production by using PCR.A total of 33 examined samples were positive for S.aureus counts represented as 13(32.5%) from drumstick samples; 11(27.5%) from thigh samples and 9(22.5%) from breast samples. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…On the other hand, higher incidence was reported by Hassanen et al (2017), Mahmoud andHamouda-Seham (2006) and Elshraway et al (2018) with 22.5, 51.5 and 53% respectively of the examined chicken fillet samples. Moreover, Saad et al (2018), Hassanen et al (2017) and Elshraway et al (2018) reported a percentage of 80, 27.5 and 45% respectively. In MDM samples nearly the same results were obtained by Kozačinski et al (2006) who detected coagulase positive S. aureus in 30.3% of the examined MDM samples.…”
Section: Resultsmentioning
confidence: 96%
“…On the other hand, higher incidence was reported by Hassanen et al (2017), Mahmoud andHamouda-Seham (2006) and Elshraway et al (2018) with 22.5, 51.5 and 53% respectively of the examined chicken fillet samples. Moreover, Saad et al (2018), Hassanen et al (2017) and Elshraway et al (2018) reported a percentage of 80, 27.5 and 45% respectively. In MDM samples nearly the same results were obtained by Kozačinski et al (2006) who detected coagulase positive S. aureus in 30.3% of the examined MDM samples.…”
Section: Resultsmentioning
confidence: 96%